Integritas dan Corporate Branding pada Tayangan Web Series Solusi BCA - Nabila, Shelly Anisa; Alamiyah, Syifa Syarifah; Winarti, Oktifani (UNIVERSITAS 17 AGUSTUS 1945 JAKARTA, 2024)
AbstractThe era of new media has revolutionized the way we communicate and access information through digital technology. Social media platforms like YouTube play a key role in digital culture by providing easy access for users to share videos. One type of content that has grown on YouTube is the web series, which is similar to TV shows but shorter in duration and divided into several episodes. Web series are now widely used as a communication strategy by many companies, including in Indonesia, which has great potential for development due to the high interest in YouTube. This study analyzes the representation of the value of integrity in the YouTube web series